Zeolite NaA as an additive in enhancing the performance of absorption refrigeration system - Hassan, Zulkafli Bin (2008)
The reversible Carnot cycle process using to obtained the optimum coefficient of performance (COP) and ammonia/water ratio. In this experiment the refrigerant is anhydrous ammonia and the absorber is water and ammonia/water ratios used are in the range of 5% to 30% ammonia in water base on volume percentage in the solution. Assuming the absorption unit has complete cycle and stable system after 8 hours and the performance of the absorption chillers unit is constant for each experiment the value of coefficient of performance COP is calculated for each hour depending on the refrigerant/absorber ratio. The COP increased with increasing generator temperature and with decreasing absorber and condenser temperatures for all the systems. Also, the lowest temperature at the evaporator is important in order to control the temperature for all the system cycle that affects the value of COP in absorption chillers. In conclusion, the optimum ammonia/water ratios that obtained in this experiment are 30% ammonia purity with 2.97 coefficient of performance. Then, to increase the performance of absorption refrigeration system Zeolite NaA was added. in the ammonia water solution with different concentration in the range 0.0002M to 0.001M. The optimum concentration of additive is determined by referring to the lowest cooling box temperature which will give the lowest value of coefficient of performance (COP). The optimum concentration of additive that can be added to the absorption process is 0.0006M of Zeolite NaA. The optimum coefficient is 1.5 compare to the coefficient of performance for absorption without additive that is only 1.2.